1984
DOI: 10.1017/s0025727300035687
|View full text |Cite
|
Sign up to set email alerts
|

Rinderpest and mainstream infectious disease concepts in the eighteenth century

Abstract: Bacteriology became an established academic discipline with the discoveries and the subsequent classification of a number of pathogenic bacteria during the latter half of the nineteenth century. The first attempt to trace the historical background to this new development appeared as early as 1887 as a series of lectures given by Friedrich Loffler and dedicated to his mentor Robert Koch.' LoMffer paid only scant attention to developments prior to 1800, although he was more appreciative of the work of Athanasius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Rinderpest has had a profound influence on public health. The 19th century devastation of Africa by rinderpest was preceded by a century of recurring European epizootics and panzootics that led to an estimated 20% loss of dairy cattle, undoubtedly retarding economic development and increasing poverty, malnutrition, and the infectious diseases that follow [25,26]. Rinderpest is alleged to have been imported from Europe into the United States in the 1860s but did not become established [27,28].…”
mentioning
confidence: 99%
“…Rinderpest has had a profound influence on public health. The 19th century devastation of Africa by rinderpest was preceded by a century of recurring European epizootics and panzootics that led to an estimated 20% loss of dairy cattle, undoubtedly retarding economic development and increasing poverty, malnutrition, and the infectious diseases that follow [25,26]. Rinderpest is alleged to have been imported from Europe into the United States in the 1860s but did not become established [27,28].…”
mentioning
confidence: 99%
“…She did collect enough specimens, notes, and sketches for a book, yet had hoped to stay longer. Illness, the heat, and humidity forced her to return to Amsterdam (Wettengl 1998 e , f ). Leeuwenhoek's letters inspired her to study her insects with a magnifying glass, and she reported on details she discovered by doing so.…”
mentioning
confidence: 99%
“…He was already studying the epidemiology of influenza and malaria, and his publication suggested quarantine, isolation, and slaughter of infected cattle, which was effective when rinderpest reached the Papal States (1715). Following Fracastoro and Rammazzini, he believed in inanimate agents of infection (Wilkinson 1984, 1992:38–44). In another work, De noxiis paludum effluviis (1717), Lancisi recommended draining swamps to eliminate both noxious air that caused malaria and “maligna insecta” (Futcher 1936:547–548, passages translated in Kean et al1978, I:22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such was the havoc wrought in France that the Controller‐General of Finances, Henri Bertin, advanced funds to Claude Bourgelat to establish in 1762 what became the first modern veterinary school in Lyon because he needed a cadre of trained manpower in rural areas to combat the ravages of rinderpest in draught oxen. 1 Within 20 years most European governments founded similar establishments for the same purpose.…”
mentioning
confidence: 99%